THE EFFECTS OF PROCESS IMPROVEMENT ON SUSTAINABLE SUPPLY CHAIN MANAGEMENT PERFORMANCE - Çiçek, Hasan; Turan, Hakan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
This study examines the effects of process improvement on sustainable supply chain management performance via the SCOR model using Lean Six Sigma tools. The transportation company is used as a case study. The critical success factors and reasons for the use of tools are reviewed. In research, it is found that process improvement increases the effectiveness of supply chain management. In addition, sustainability plays a major role in supply chain management. To measure and improve the effectiveness of this model, Lean Six Sigma tools have been used. The paper concludes that firms can have savings in terms of money and time. Furthermore, it is proved that CO2 emissions could be reduced. This paper prompts the efficacy of well-publicized methodologies and evaluates their implementation for process improvement for the firms. The practical application, constraints, and resultant effects of developing Lean Six Sigma were reviewed to give impetus to the methodology.